2013
DOI: 10.2147/dddt.s40129
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and antioxidant activity of novel 4-substituted phenyl-2,2'-bichalcophenes and aza-analogs

Abstract: Evaluation of the potential antimutagenic activities of new compounds by Ames assay has been of great interest for the development of novel therapeutics for many diseases including cancer. Ten novel bichalcophenes with in vitro and in vivo broad spectrum activities against various microbial strains were investigated throughout the present study for their cytotoxic, antioxidant, and antimutagenic potential in a Salmonella reverse mutation assay system against sodium azide (NaN3) and benzo[a]pyrene (B[a]P). At n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Since both the mutagens and carcinogens may act through the generation of reactive oxygen species, the discovery and exploration of plant extracts/phytocompounds possessing both antioxidant and antimutagenic properties are of great practical and therapeutic significance. It is presumed that medicinal plants those are good in antioxidant activity could also show antimutagenic activity and such natural products could reduce or inhibit the mutagenic potential of mutagens and/or procarcinogens (El-Sayed & Hussin, 2013;Garg et al, 2008). However, antimutagenic and anticarcinogenic activities of bioactive compounds can also act by direct action (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since both the mutagens and carcinogens may act through the generation of reactive oxygen species, the discovery and exploration of plant extracts/phytocompounds possessing both antioxidant and antimutagenic properties are of great practical and therapeutic significance. It is presumed that medicinal plants those are good in antioxidant activity could also show antimutagenic activity and such natural products could reduce or inhibit the mutagenic potential of mutagens and/or procarcinogens (El-Sayed & Hussin, 2013;Garg et al, 2008). However, antimutagenic and anticarcinogenic activities of bioactive compounds can also act by direct action (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Humans are provided with many defences and their failure could lead to DNA damage and consequently to cancer (El-Sayed and Hussin, 2013). Carcinogenesis is generally a slow process and often takes decades from tumor initiation to diagnosis, offering a considerable time frame for chemopreventive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Various recent reports state that the natural antioxidants may reduce or inhibit the mutagenic potential of mutagens and carcinogens (Cardador-Martínez et al, 2006;El-Sayed & Hussin 2013). Zahin et al (2010) have reported that the anticarcinogenic and antimutagenic activities of medicinal and food plants are executed mainly by scavenging of free radicals.…”
Section: Discussionmentioning
confidence: 99%